Rosendaal linear interpolation method appraising of time in therapeutic range in patients with 12-week follow-up interval after mechanical heart valve replacement - Zhu, Xiliang; Xiao, Xijun; Wang, Sheng; Chen, Xianjie; Lu, Guoqing; Li, Xiaoyang (Frontiers in Cardiovascular Medicine, 2022)
Background: The objective of this study was to evaluate the quality of anticoagulation by the time in therapeutic range (TTR) for patients with 12-weeks INR follow-up interval. Methods: From January 2018 to December 2020, a selective group of patients who underwent mechanical valve replacement and followed up at our anticoagulation clinic for adjustment of warfarin dose were enrolled into this study. The incidences of anticoagulation-related complications were reported by linearized rates. TTR was calculated by the Rosendaal linear interpolation method. Results: Two hundred and seventy-four patients were eligible in this study. Mean age of these patients was 52.8 ± 12.7 years, 65.7% (180) of them were females. The mean duration of warfarin therapy was 16.7 ± 28.1 months. A total of 1309 INR values were collected, representing 66789 patient-days. In this study, the mean TTR was 63.7% ± 18.6%, weekly doses of warfarin were 20.6 ± 6.0 mg/weekly, and the mean monitoring interval for patient was 53.6 ± 27.1 days. There were 153 cases in good TTR group (TTR ≥ 60% ), and 121 cases in poor TTR group (TTR < 60%). The calculated mean TTR in both groups were 42.6% ± 22.1% and 74.8% ± 10.4%, respectively. Compared with the TTR≥60% group, the TTR < 60% group exhibited a more prevalence of female gender (p = 0.001), Atrial fibrillation (p < 0.001), NYHA ≥ III (p < 0.001) and lower preoperative left ventricular ejection fraction (LVEF, p = 0.032). In multivariate analysis, female gender (p = 0.023) and atrial fibrillation (p = 0.011) were associated with TTR < 60%. The incidence of major bleeding and thromboembolic events was 2.7% and 1.1% patient-years, respectively. There was one death which resulted from cerebral hemorrhage. The incidence of death was 0.5% patient-years. The difference of anticoagulation-related complications between the TTR < 60% group and the TTR ≥ 60% group was not statistically significant Conclusion: For patients with stable international normalized ratio monitoring results who are follow-up at anticoagulation clinics, a 12-weeks monitoring interval has an acceptable quality of anticoagulation. The female gender and atrial fibrillation were associated with TTR < 60%.